Building a bridge to the future: teacher perspectives on indigenous language education - Velma M. Hale; Louise Lockard (International Journal of Educational Research Open, 2022)
This article addresses the histories of two Indigenous language immersion schools from the perspectives of teachers in the programs. The research questions, “What is the place of stories of our families, and communities? What does it mean to negotiate our place within the world of traditional stories told by our elders in the hogan and between worlds in the classroom?” draw on the histories of these programs to critique constructions of mainstream schooling and to frame the Dine epistemology as central to these narratives of teachers in the immersion classroom.